Naval discipline, storms and basic principles of international law in the XIX century: The Monsoon case - Céspedes, Rodrigo (Derecho Público Iberoamericano, 2021)
During the 19th century, the Valparaíso court affirmed its extraterritorial jurisdiction to investigate torments administered by the captain of a US-flagged ship based on the extreme seriousness of the denounced facts that were in conflict with the basic principles of civilization and humanity.